En el camino. En busca de los arrieros novohispanos - Hausberger, Bernd (El Colegio de México, A.C., 2014)
This work deals with the many-faced world of transportation. It seeks for a bottom-up perspective on the history of New Spain throughout its three centuries of viceroyalty. Its aim is to show that arrieros or mule riders did not form a solid group, suggesting instead that many people worked mule trains for short periods of time. The author insists on the need to examine arrieros within the context of groups and individuals who, like them, constantly moved from one place to another. This trait is probably typical of many castes, who thus evaded New Spain's rigidly hierarchical society. In order to sustain this idea and fix a starting line for the social-cultural history of arrieros, the author introduces a series of data, both qualitative ad quantitative, regarding means of transportation, the people operating them, and their lifestyles.